The Development of Teaching Materials Based on Research of Shisha Cigarettes Exposure Reproductive System Materials as a Learning Source of High School Students - Mufidah, Fadhilatunnisa; Lisdiana, Lisdiana (Journal of Biology Education, 2021)
The Research and Development aims to determine the feasibility and effectiveness of using research-based teaching materials supplements as a source of learning for high school students. The learning resources developed are in the form of research-based teaching materials. The method used in this study uses research steps from Sugiyono (2015) that have been modified. The indicators used in this study are indicators of feasibility and effectiveness. Indicators of eligibility in this study involve material and media validity, student and teacher responses. The results of the research have shown that research-based teaching materials are feasible and effective to be used as a source of learning for students. The results of the validity of the material and media are in very valid criteria with each score 85% and 96.875%, while the responses of students and teachers are in the criteria of a good readability level with the value of 88.4 % and 80%. The developed teaching materials are also effective, this can be seen from the classical completeness of the class obtained a score of 83% and an increase in the results of the N-gain test that there are â‰¥ 70% of students who get N-gain scores with moderate to high criteria.